Sea-time : an ethnographic adventure - Sampson, H. (Routledge, 2024)
"This book is an ethnography that draws upon 23 years of qualitative research and shipboard field work in the merchant cargo shipping sector. It explores the lives and work of seafarers and how these have changed over time. Change over time and the experience of time on board are organising themes throughout the text. They are contextualised with accounts of transformation in the regulation of the shipping industry and technological innovation. The book begins with a unique account of a voyage on a container ship. In this, the author details both the research process and the daily activities and shared thoughts of the seafarers who are on board. The narrative is further enhanced with illustrative examples taken from other voyages to illustrate continuities and change over time. The book will be of value to individuals, scholars, and researchers interested in ethnography of all kinds. Sociologists, anthropologists, maritime studies students, seafarers, ship operators, and policy makers will find the text engaging and revealing. It provides a vivid account that will appeal to academics interested in the study of work, workplace change and time. It is accessibly written and will be enjoyed by readers interested in the contemporary shipping industry, and the life and work of seafarers"-- Provided by publisher.
Keywords: Merchant marine -- History.; Merchant ships -- History.; Sailors -- History.; Shipping -- History.; elektronické knihy; electronic books